2021
DOI: 10.3892/mmr.2021.12072
|View full text |Cite
|
Sign up to set email alerts
|

ROS‑associated mechanism of different concentrations of pinacidil postconditioning in the rat cardiac Nrf2‑ARE signaling pathway

Abstract: Previous studies have confirmed that 50 µmol/l pinacidil postconditioning (PPC) activates the nuclear factor-E2 related factor 2 (Nrf2)-antioxidant responsive element (ARE) pathway, which protects the myocardium from ischemia-reperfusion (IR) injury; however, whether this is associated with reactive oxygen species (ROS) generation remains unclear. In the present study, a Langendorff rat model of isolated myocardial IR was established to investigate the mechanism of PPC at different concentrations, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…When oxidative stress occurs, Nrf2 dissociates from Keap1, and Nrf2 enters the nucleus to combine with antioxidant response elements (ARE) [ 8 ], activate downstream related genes, and promote the expression of a variety of enzymes and nonenzyme antioxidant genes, including heme oxygenase 1 (HO-1), SOD, glutathione peroxidase, quinone oxidoreductase 1 (NQO-1), and catalase (CAT), to enhance cell resistance to oxidative damage stress ability [ 9 ]. Some studies [ 10 ] believe that the use of Nrf2, an excitatory drug, pinacidil, can significantly increase the antioxidative stress of the cardiology and improve myocardial function. The mechanism is that the expression of Nrf2 protein is upregulated after the above treatment, thereby activating the Nrf2/ARE pathway, exerting its antioxidative stress effect.…”
Section: Introductionmentioning
confidence: 99%
“…When oxidative stress occurs, Nrf2 dissociates from Keap1, and Nrf2 enters the nucleus to combine with antioxidant response elements (ARE) [ 8 ], activate downstream related genes, and promote the expression of a variety of enzymes and nonenzyme antioxidant genes, including heme oxygenase 1 (HO-1), SOD, glutathione peroxidase, quinone oxidoreductase 1 (NQO-1), and catalase (CAT), to enhance cell resistance to oxidative damage stress ability [ 9 ]. Some studies [ 10 ] believe that the use of Nrf2, an excitatory drug, pinacidil, can significantly increase the antioxidative stress of the cardiology and improve myocardial function. The mechanism is that the expression of Nrf2 protein is upregulated after the above treatment, thereby activating the Nrf2/ARE pathway, exerting its antioxidative stress effect.…”
Section: Introductionmentioning
confidence: 99%
“…e pathogenesis and progression of various cardiovascular diseases are associated with close apoptosis and the inhibition or activation of related signaling pathways. Studies have shown that Nrf2/ ARE signaling pathway, as an important endogenous antioxidant signaling pathway, plays an antioxidant and cardiac protection role after myocardial ischemia-reperfusion [15][16][17]. Activation of JAK2/STAT3 pathway has also been shown to reduce MIRI in rats [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that drug postconditioning could significantly improve the function of the left ventricular [ 30 ]. Our cardiac function results showed that urocortin I could increase cardiac contractility, reduce left ventricular and systolic volume, and improve cardiac function during MIRI.…”
Section: Discussionmentioning
confidence: 99%